Propylene Glycol Liposomes as a Topical Delivery System for Miconazole Nitrate: Comparison with Conventional Liposomes - Elmoslemany, Riham M. (Springer US, 2012)
Propylene glycol (PG)-phospholipid vesicles have been advocated as flexible lipid vesicles for enhanced skin delivery of drugs. To further characterize the performance of these vesicles and to address some relevant pharmaceutical issues, miconazole nitrate(MN)-loaded PG nanoliposomes were prepared and characterized for vesicle size, entrapment efficiency, in vitro release, and vesicle stability. An issue of pharmaceutical importance is the time-dependent, dilution-driven diffusion of propylene glycol out of the vesicles. This was addressed by assessing propylene glycol using gas chromatography in the separated vesicles and monitoring its buildup in the medium after repeated dispersion of separated vesicles in fresh medium. Further, the antifungal activity of liposomal formulations under study was assessed using Candida albicans, and their in vitro skin permeation and retention were studied using human skin. At all instances, blank and drug-loaded conventional liposomes were included for comparison. The results provided evidence of controlled MN delivery, constant percent PG uptake in the vesicles (≈45.5%) in the PG concentration range 2.5 to 10%, improved vesicle stability, and enhanced skin deposition of MN with minimum skin permeation. These are key issues for different formulation and performance aspects of propylene glycol-phospholipid vesicles.